Competitive Equilibria in Two-Sided Matching Markets with General Utility Functions - Alaei, Saeed; Jain, Kamal; Malekian, Azarakhsh (Operations Research, 2016)
We present an exact characterization of utilities in competitive equilibria of two-sided matching markets in which the utility of each agent depends on the choice of partner and the terms of the partnership, potentially including monetary transfer. Examples of such markets include sellers and buyers or jobs and workers. Demange and Gale showed that the set of competitive equilibria in this type of market forms a complete lattice with each extreme point of the lattice representing an equilibrium with the highest utilities for the agents on one side and the lowest utilities for the agents on the opposite side. Our characterization is based on establishing a connection between the competitive equilibria of a market and the competitive equilibria of certain strict subsets of that market—each obtained by removing exactly one agent. This characterization captures the effect of competition when agents are added to the market or removed from the market. It gives a precise procedure for constructing competitive equilibria and provides a constructive proof of existence of such equilibria; in contrast, previous proofs have been based on fixed point theorems.